Two new species of Begonia (Begoniaceae) from the Colombian Western Cordillera - Jara-Muñoz, O. A. (Phytotaxa, 2016)
Two New species of Begonia section Semibegoniella (C.DC) Barkley & Baranov (Begoniaceae) are described from the Colombian Western Cordillera. Illustrations of distinguishing characters, photos of living plants and a key to the Colombian Begonias with tepals fused are included.